An Analysis of Paths of Economic Development of Poland’s Regions - Batóg, Jacek; Dmytrów, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The research consists of two stages. The first provides a comparative analysis of the level of economic development of Polish voivodships for the period 2000–2013. The second evaluates how similar the paths of economic development of individual regions are. To achieve the latter end, measures of the similarity of time series were applied, particularly dynamic time warping. The starting point for this method is to compute a matrix of costs containing the distances between all the elements of the time series to be analysed (pairwise). The optimum path between the starting and the final points may then be found. This path is characterised by the minimum value of the cumulated distances. The results evidence strong similarities in dynamics and high differences in the level of economic development of Polish voivodships and can be useful for the programming of regional policy, especially for determining whether the foundations for common programmes of the cohesion policy for given groups of regions exist.